ANALISIS KONTRIBUSI MASYARAKAT PETANI PESISIR TERHADAP KETAHANAN PANGAN RUMAH TANGGA DI ERA ADAPTASI KEBIASAAN BARU (Studi Kasus di Desa Jarangan, Kec. Rejoso, Kab. Pasuruan) - Abi Subekti, Bagas; Brillian Pintakami, Lintar; Widiatmanta, Jeka (grafting, 2022)
This study aims to describe the agribusiness management of coastal farming communities, identify the contribution of male and female farmers and analyze coastal farming businesses in order to help maintain regional food security. The results of the study show that pond agribusiness management is carried out traditionally in the saprodi and production subsystems. The contribution of coastal farmers to household resilience is dominated by male farmers in pond management with a percentage of 74% and female farmers 36%. Coastal farmers who work on ponds are able to meet their daily food needs. Sourced from the results of milkfish farming and wild shrimp fishing. The income obtained from these results of Rp. 6,295,712 per season or Rp. 2,098,570 per month can meet their other basic needs every month in this New Habit Adaptation Era.